Penerapan Metode The Learning Cell untuk Meningkatkan Hasil Belajar Tematik Siswa - Saimaita, Saimaita; Soniyar, Gina; Rejeki, Rejeki (Edusia: Jurnal Ilmiah Pendidikan Asia, 2023)
This study aims to determine the increase in thematic learning outcomes after applying The Learning Cell method to class VI students in the odd semester of the 2021/2022 academic year at SD Negeri 001 Bangun Purba. This research is a Classroom Action Research with the research subject being the sixth-grade students of SD Negeri 001 Bangun Purba for the academic year 2021/2022, totaling 21 people. The data of this study on learning outcomes in the cognitive, affective, and psychomotor domains were collected using test and observation methods. Data were analyzed using quantitative descriptive analysis. The results obtained are the average percentage of learning outcomes in the first cycle of 73.70%, which is in the medium category, and the second cycle, it becomes 80.19%, which is in the high category. This shows an increase in the average percentage of student learning outcomes from cycle I to cycle II of 6.49%. In the affective domain, in the first cycle, the average percentage is 77%, and in the second cycle, it is 81%, which is in the active category. Thus, applying The Learning Cell method can improve the thematic learning outcomes of sixth-grade students in the odd semester of SD Negeri 001 Bangun Purba for the 2021/2022 academic year.